Investigation of the outcome of pregnancies complicated by increased fetal movements and their relation to underlying causes – A prospective cohort study. (3rd August 2020) - Sharp, Imogen; Adeyeye, Temidayo; Peacock, Linda; Mahdi, Amy; Farrant, Kimberley; Sharp, Andrew N.; Greenwood, Susan L.; Heazell, Alexander E. P.
Abstract: Introduction: Retrospective studies have reported an association between a single episode of significantly increased fetal movements (IFMs) and stillbirth after 28 weeks' gestation. This prospective study aimed to report the outcome of pregnancies associated with maternal perception of IFMs and determine whether this symptom is associated with adverse pregnancy outcome, a pathological intrauterine environment or placental dysfunction. Material and methods: Women reporting IFMs after 28 weeks' gestation were recruited from St Mary's Hospital, Manchester and Liverpool Women's Hospital, UK, between 1 November 2017 and 1 May 2019. Demographic and clinical information were obtained and an ultrasound scan was performed to assess fetal biometry, liquor volume and umbilical artery Doppler. Maternal serum samples were collected for analysis of placentally derived biomarkers using ELISA. After delivery, maternal and fetal outcome data were collected and placentas and umbilical cord blood were obtained for analysis using immunohistochemistry and ELISA, respectively. Placental and serum samples were matched by gestation and maternal characteristics to participants with normal fetal activity. Results: Seventy‐seven women presented with IFM, representing 0.45% of the maternity population; 64 women consented to participate in the study, of which 7 (10.9%) experienced adverse pregnancy outcome: birthweight <3rd centile, 2 (3.1%); pH ≤7.10, 1 (1.6%); neonatal intensive care unit admission, 4 (6.3%). Women had IFM for varying lengths of time before presenting: 17.2% had IFM for less than 1 hour and 29.7% reported IFM lasting longer than 24 hours. Four women (6.3%) had abnormalities of the fetal heart rate trace on assessment. Women with IFM had similar modes of birth to women giving birth in participating maternity units. There was no evidence of macroscopic placental or umbilical cord abnormalities, alterations in microscopic placental structure, placental endocrine dysfunction or intrauterine hypoxia or infection in women with IFM compared with controls. Conclusions: This prospective study did not find evidence of an association between IFM and adverse pregnancy outcome. It also did not find evidence of underlying placental dysfunction, cord anomalies, intrauterine hypoxia or infection in pregnancies with IFM. Further work is required to determine the strength of association between IFM and adverse pregnancy outcome and its origins. At present, IFM cannot be used to identify fetuses at increased risk of adverse outcome.